The Influence of Differentiation and Low-Cost Strategies through Value Creation Strategy on Competitive Advantage at Integrated Islamic Junior High Schools in Riau Islands Province - Asrulla, Asrulla; Risnita; Mahmud MY (Darul Ilmi Bina Insan Foundation, 2025)
In the context of educational institutions, especially Islamic schools, strategic management and marketing play a vital role in building competitive advantage. This quantitative study aims to examine the influence of differentiation and low-cost strategies on competitive advantage through a value creation strategy at Integrated Islamic Junior High Schools in Riau Islands Province. The research contributes to the field of Islamic Educational Management, particularly in strategic educational management with a focus on institutional marketing. Data were collected through a survey of 122 respondents, selected using purposive sampling, and analyzed using path analysis. The findings reveal that differentiation and low-cost strategies have both direct and indirect impacts on value creation and competitive advantage. Moreover, the value creation strategy functions as a mediating variable, enhancing the effect of differentiation and low-cost strategies on competitive outcomes. The study concludes that strengthening differentiation, improving cost efficiency, and implementing effective value creation strategies are essential for increasing the competitive advantage of educational institutions in the Islamic education sector.